Effect of intravenous infusion of insulin in diabetics with acute myocardial infarction. Issue 6491 (3rd August 1985) - Clark, R S; English, M; McNeill, G P; Newton, R W
Abstract : Diabetes mellitus is associated with a high mortality after myocardial infarction. To see whether this may be decreased by improved diabetic control the effect of an insulin infusion regimen was studied in patients with acute myocardial infarction. From April 1982 to April 1983, 33 diabetics were admitted with acute myocardial infarction. Those being treated with diet alone or oral hypoglycaemic drugs continued with this unless control was poor, when they were changed to a "sliding scale" regimen of subcutaneous insulin injections thrice daily. Those already receiving insulin were maintained on thrice daily subcutaneous injections. From April 1983 to April 1984, 29 diabetics had acute myocardial infarction. Those receiving treatment with oral hypoglycaemic drugs or insulin were changed to continuous intravenous infusion of insulin, the aim being to maintain the blood glucose concentration at 4-7 mmol/I (72-126 mg/100 ml). Those being treated with diet alone continued with this if blood glucose concentrations were acceptable. Total mortality fell from 42% in the first year to 17% in the second (p less than 0.05). Over the same period mortality among non-diabetic patients with myocardial infarction did not change significantly. There was a significant fall in cardiac arrhythmias (expressed as the percentage of patients in whom arrhythmias were recorded) from 42% to 17% (p less than 0.05). The most significant fall in the incidence of complications occurred in those who had been receiving oral hypoglycaemic drugs on entry to the study (87% to 50%, p less than 0.05).